2014
DOI: 10.1259/bjr.20130676
|View full text |Cite
|
Sign up to set email alerts
|

Defining normoxia, physoxia and hypoxia in tumours—implications for treatment response

Abstract: Tumour hypoxia is increasingly recognized as a major deleterious factor in cancer therapies, as it compromises treatment and drives malignant progression. This review seeks to clarify the oxygen levels that are pertinent to this issue. It is argued that normoxia (20% oxygen) is an extremely poor comparator for "physoxia", i.e. the much lower levels of oxygen universally found in normal tissues, which averages about 5% oxygen, and ranges from about 3% to 7.4%. Importantly, it should be recognized that the media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
752
2
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 803 publications
(782 citation statements)
references
References 118 publications
21
752
2
7
Order By: Relevance
“…Numerous studies have demonstrated an association between the magnitude of intratumoral hypoxia and the outcome of cancer treatment. [3][4][5][6][7][8] This association has also been shown for PDAC, where a more hypoxic phenotype is associated with a worse prognosis. 38,39 We hypothesize that the clinical outcome for patients treated with the triplet treatment may be more favorable than doublet nab-paclitaxel and gemcitabine, given the multiple therapeutic modalities employed including hypoxia-selective targeting.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Numerous studies have demonstrated an association between the magnitude of intratumoral hypoxia and the outcome of cancer treatment. [3][4][5][6][7][8] This association has also been shown for PDAC, where a more hypoxic phenotype is associated with a worse prognosis. 38,39 We hypothesize that the clinical outcome for patients treated with the triplet treatment may be more favorable than doublet nab-paclitaxel and gemcitabine, given the multiple therapeutic modalities employed including hypoxia-selective targeting.…”
Section: Discussionmentioning
confidence: 95%
“…[1][2][3][4] Published studies show that the magnitude and extent of tumor hypoxia correlate directly with poor clinical prognosis. 5 The basis for the correlation between tumor hypoxia and prognosis has been ascribed to both therapeutic treatment failure and hypoxia-induced pro-metastatic potential.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the relative effect of each on transcription of ORE-containing genes may change continuously as oxygen levels decline. Experimental oxygen tension is 20% although this is high compared to physiological levels in vivo, which range from ~3% to 8% in most tissues and ~13% in lung (19,34). One of the most critical periods of oxygen sensing is during placental development where oxygen levels switch from 2-3% prior to 12 weeks of gestation to 8% afterwards (35).…”
Section: Discussionmentioning
confidence: 99%
“…Other parameters important for maintaining the culture usually are 100% humidity and temperature of 37°C. Even though it is now commonly known that this oxygen concentration is similar to the atmospheric one and therefore is almost two to ten-fold higher than maintained in the blood [16], various authors still consider 21% of oxygen in culture gas mixture as a normal condition and regard all lowered oxygen contents as hypoxic ones [17]. We fully support the view of Atkuri et al [18] that only conditions of in vitro experiments closely mimicking the physiological ones, also with respect to the oxygen concentration, would allow to explore the actual in vivo processes and that such conditions should be used wherever possible.…”
Section: Introductionmentioning
confidence: 99%